Adsorption of Benzene by "green" functionalization of Montmorillonite - Anjum, H. (EDP Sciences, 2018)
The capacity of organically modified Montmorillonite (MMT) clay to adsorb nonpolar organic compound (benzene) in an aqueous solution, was investigated under the batch process. MMT was pretreated (centrifuged) and then functionalized with green intercalating agent i.e. 1-hexyl-3-methyl imadazolium chloride HMimCl. The characterization through Fourir Transoform Infrared Spectroscopy (FTIR), Differential Scanning Calorimeter (DSC) and Field Emission Scanning Electron Microscope (FE-SEM) confirmed the presence of the oxygen containing functional groups, changes in melting point and variation in the morphological properties. The governing parameters for the sorption of benzene such as the effect of contact time, pH, adsorbent dose and rotation were studied. The kinetic data conformed to pseuodo 2nd order kinetic model and the isotherm experimental data were a better fit to Langmuir model with maximum adsorption capacity of 588.23mg/g under experimental conditions. Overall, MMT intercalated with 1-hexyl-3-methyl imadazolium chloride is a promising environmental friendly adsorbent for the abatement of benzene in an aqueous solution. Â© The Authors, published by EDP Sciences, 2018.